Expression of human epileptic temporal lobe neurotransmitter receptors in Xenopus oocytes: An innovative approach to study epilepsy - Palma, Eleonora (National Academy of Sciences, 2002)
Poly(A(+)) RNA was extracted from the temporal lobe (TL) of medically intractable epileptic patients which underwent surgical TL resection. Injection of this mRNA into Xenopus oocytes led to the expression of ionotropic receptors for γ-aminobutyric acid (GABA), kainate (KAI) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA). Membrane currents elicited by GABA inverted polarity at −15 mV, close to the oocyte's chloride equilibrium potential, were inhibited by bicuculline, and were potentiated by pentobarbital and flunitrazepam. These basic characteristics were also displayed by GABA currents elicited in oocytes injected with mRNAs isolated from human TL glioma (TLG) or from mouse TL. However, the GABA receptors expressed by the epileptic TL mRNA exhibited some unusual properties, consisting in a rapid current run-down after repetitive GABA applications and a large EC(50) (125 μM). AMPA alone evoked very small or nil currents, whereas KAI induced larger currents. Nevertheless, upon cyclothiazide treatment, AMPA elicited substantial currents that, like the KAI currents, were inhibited by 6-cyano-7-nitroquinoxaline-2,3-dione (CNQX). Furthermore, the glutamate receptor 5 (GluR5) agonist, ATPA, failed to evoke an obvious current although both RT-PCR and Western blot analyses showed GluR5 expression in the epileptic TL. Oocytes injected with mouse TL or human TLG mRNAs generated KAI and AMPA currents similar to those evoked in oocytes injected with epileptic TL mRNA but, in contrast to these, the mouse TL and human TLG oocytes were also responsive to ATPA. Our findings are in accord with the concept that both a depression of GABA inhibition and a dysfunction of the KAI-receptor system maintain a high neuronal excitability that results in epileptic seizures.